Efektifitas Program Bantuan Ternak Sapi Potong Sebagai Salah Satu Strategi Penganggulangan Kemiskinan Di Kabupaten Padang Pariaman - Devi Yanti; Asdi Agustar; Rusda Khairati (Jurnal Niara, 2023)
The purpose of this study was to determine the benefits of the beef cattle assistance program from the aspect of employment, the addition of cash and non-cash values ​​and to determine the effectiveness of the beef cattle assistance program in improving the economy of the Padang Pariaman district community. This research used survey method and analyzed with descriptive statistics. From the research, it was found that the Beef Cattle Assistance Program was able to absorb family labor as follows: assistance for 1-2 cows absorbs labor Male 0.32 HKP, female 0.27 HKP, for assistance 3-4 beef cattle absorb labor male 0.69 HKP and female 0.28 HKP, while for the assistance of cows above 5 heads, male labor is 0.57 HKP, female is 0.35 HKP and child labor is 0.21 HKP. Assistance for 1 cow that is raised for 7 years, the total cash and non-cash value is Rp. 431.174/month. For those raised for 5 years, the total value of cash and non-cash is Rp. 781,981/month. while cows raised for 3 years total added value of Rp 277,778/month. Assistance with 2 cows that were reared for 7 years, the total added value obtained was Rp. 713,245/month and those raised for 5 years, the total value of steadfastness was Rp. 1120,000/month. for bulls of 3 or more cows with a maintenance period of 7 years, the total added value obtained is Rp. 682.589 / month. The beef cattle assistance program has not been effective in improving the economy of the community in Padang Pariaman distric